Signal transfer in human protein tyrosine phosphatase PTP1B from allosteric inhibitor P00058. Issue 24 (26th December 2022) - Chirgadze, Yuri N.; Battaile, Kevin P.; Likhachev, Ilya V.; Balabaev, Nikolay K.; Gordon, Roni D.; Romanov, Vladimir; Lin, Andres; Karisch, Robert; Lam, Robert; Ruzanov, Max; Brazhnikov, Evgeniy V.; Pai, Emil F.; et al.
Abstract: Protein tyrosine phosphatases constitute a family of cytosolic and receptor-like signal transducing enzymes that catalyze the hydrolysis of phospho-tyrosine residues of phosphorylated proteins. PTP1B, encoded by PTPN1, is a key negative regulator of insulin and leptin receptor signaling, linking it to two widespread diseases: type 2 diabetes mellitus and obesity. Here, we present crystal structures of the PTP1B apo-enzyme and a complex with a newly identified allosteric inhibitor, 2-(2, 5-dimethyl-pyrrol-1-yl)-5-hydroxy-benzoic acid, designated as P00058. The inhibitor binding site is located about 18 Å away from the active center. However, the inhibitor causes significant re-arrangements in the active center of enzyme: residues 45–50 of catalytic Tyr-loop are shifted at their Cα-atom positions by 2.6 to 5.8 Å. We have identified an event of allosteric signal transfer from the inhibitor to the catalytic area using molecular dynamic simulation. Analyzing change of complex structure along the fluctuation trajectory we have found the large Cα-atom shifts in external strand, residues 25–40, which occur at the same time with the shifts in adjacent catalytic p-Tyr-loop. Coming of the signal to this loop arises due to dynamic fluctuation of protein structure at about 4.0 nanoseconds after the inhibitor takes up its space. Communicated by Ramaswamy H. Sarma